Nuclear Security Dilemma of Pakistan - Iram Khalid (Journal of Political Studies, 2013)
The issue of nuclear escalation is neither simple, nor straightforward in the context of the South Asian region. This is mainly because this region is a home to two inherently rival nuclear states. Nuclear equation in South Asia is not quite simple to comprehend the changing political and strategic scenario of this region. After 1998, both India and Pakistan moved towards a stage where slight negligence and irresponsible behavior can result huge devastation in the entire region. Moreover, the risk of attaining the nuclear material through espionage in both states can lead to a disastrous outcome where the non state actors and the terrorist organizations are operating to challenge the status quo. Nuclear weapons ensure the security of the state on one hand and on the other, risk of nuclear war casts a deep shadow over the region. Both India and Pakistan has to think out of box solutions to lessen the dangers of a nuclear holocaust. The study concludes that existing nuclear security culture in Pakistan is appropriate .International community should preempt any situation of escalation between the two, rather than engaging in “firefighting.”